2015
DOI: 10.1159/000369608
|View full text |Cite
|
Sign up to set email alerts
|

Selecting Appropriate Dose Regimens for AM-101 in the Intratympanic Treatment of Acute Inner Ear Tinnitus

Abstract: Inhibition of cochlear N-methyl-D-aspartate (NMDA) receptors with AM-101, a small molecule antagonist delivered by intratympanic injection, represents a novel approach to treat acute tinnitus triggered by glutamate excitotoxicity. An earlier double-blind, randomized, placebo-controlled phase II clinical trial (TACTT0) had demonstrated a significant and dose-dependent improvement in tinnitus triggered by acute acoustic trauma or otitis media from baseline to day 90. A second phase II trial (TAC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 22 publications
1
15
0
Order By: Relevance
“…The previous trials had shown good tolerance of the treatment with no impact on hearing; adverse events that were predominantly local, ear related, and transient; and minimal systemic exposure. 5 , 6 Based on almost 1400 intratympanic injections, the present study confirmed the favorable safety profile.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The previous trials had shown good tolerance of the treatment with no impact on hearing; adverse events that were predominantly local, ear related, and transient; and minimal systemic exposure. 5 , 6 Based on almost 1400 intratympanic injections, the present study confirmed the favorable safety profile.…”
Section: Discussionsupporting
confidence: 80%
“…The use of phenol was not recommended based on prior study experience. 6 Prior to study drug administration, any remaining anesthetic had to be suctioned off. The injection was to be performed in the posterior-inferior quadrant or, alternatively, in the anterior-inferior quadrant.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We did not observe large consistent decreases for the MML or loudness match measures. Use of psychoacoustic measures such as the MML have been problematic in earlier studies 39 , 40 and loudness matching is known to be subject to learning effects 41 . In this study, there was high variability in MML measurements across baselines with an average difference of 7.4 dB (range 6.2 to 29 dB), making interpretation of the results difficult.…”
Section: Discussionmentioning
confidence: 99%
“…In another study performed afterwards in 2015 on this NMDA antagonist, the best dosage was found [49]: in 16 centers in the USA and Europe, 85 patients who had tinnitus for not longer than 3 months after noise-induced hearing loss, barotrauma, acute middle ear infection, or middle ear surgery, underwent intratympanic injection of the drug or placebo in the context of a phase II study conducted in a double-blind, randomized, and placebo-controlled way. Half of the patients received one treatment, the others had 3 injections in weekly intervals (placebo or AM-101).…”
Section: Pharmacotherapy Of Tinnitusmentioning
confidence: 99%